Packaging religion through training: Da'wah commodification among middle-class muslim women in Indonesia - Uswatusolihah, Uus; Suharto, Abdul Wachid Bambang; Fuad, Muskinul; Asmaya, Enung (Jurnal Ilmu Dakwah, 2025)
Purpose – This article examines the phenomenon of the commodification of da'wah through religious training programs targeted at middle-class Muslim women in contemporary Indonesia, specifically the Spiritual Motherhood and Miracle Women trainings. Method – The study employs an ethnographic approach, collecting data through participant observation, interviews, and document analysis. Result – The results showed that distinctive patterns in these da'wah trainings: they are held in prestigious venues, involve speakers and participants predominantly from the middle class—especially women—and maintain ongoing communication networks among alums. The commodification of religion within these trainings is evident in branded material packaging, training fees and discounts, the use of celebrity figures, and book production. Implication – This study asserts that commodification serves as a means to present and frame Islamic values, reflecting the dynamics of religious adaptation within a society increasingly influenced by consumer culture. These findings encourage critical reflection on the practices and directions of da'wah in the modern era. Originality/Value – This research is the first study on packaging preaching through paid spiritual training, such as Spiritual Motherhood and Miracle Women. *** Tujuan – Artikel ini mengkaji fenomena komodifikasi da'wah melalui program pelatihan keagamaan yang ditujukan bagi perempuan Muslim kelas menengah di Indonesia kontemporer, khususnya program Spiritual Motherhood dan Miracle Women. Metode – Studi ini menggunakan pendekatan etnografis, mengumpulkan data melalui observasi partisipan, wawancara, dan analisis dokumen. Hasil – Hasil penelitian menunjukkan pola khas dalam program-program da'wah ini: diselenggarakan di tempat-tempat prestisius, melibatkan pembicara dan peserta yang sebagian besar berasal dari kelas menengah—terutama perempuan—serta mempertahankan jaringan komunikasi berkelanjutan di antara alumni. Komodifikasi agama dalam program-program ini terlihat jelas melalui kemasan materi bermerk, biaya pelatihan dan diskon, penggunaan figur selebriti, serta produksi buku. Implikasi – Studi ini menegaskan bahwa komodifikasi berfungsi sebagai sarana untuk menyajikan dan membingkai nilai-nilai Islam, mencerminkan dinamika adaptasi agama dalam masyarakat yang semakin dipengaruhi oleh budaya konsumerisme. Temuan ini mendorong refleksi kritis terhadap praktik dan arah da'wah di era modern. Orisinalitas/Nilai – Penelitian ini merupakan studi pertama yang mengkaji kemasan dakwah melalui pelatihan spiritual berbayar, seperti Spiritual Motherhood dan Miracle Women.